The protective effects of FeOx/NC nanozymes on chondrocytes by scavenging reactive oxygen species - Jianfeng GUO; Rongwei ZHANG; Zhangrui HUANG; Zhiquan PANG; Shixing LUO (Guangxi Yike Daxue xuebao, 2025)
Objective To investigate the chondroprotective effects and underlying mechanisms of iron oxidebased nanozymes (FeOx/NC) in a rat model of osteoarthritis (OA). Methods FeOx/NC nanozymes were synthesized and characterized, and their enzyme-mimetic activities resembling superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) were detected. Primary chondrocytes were isolated in vitro from SD rats and divided into four groups: control group, H2O2 group, NC+H2O2 group, and FeOx/NC+H2O2 group. The biocompatibility was assessed using the cell counting kit-8 (CCK-8) assay and Calcein-AM/PI staining, and reactive oxygen species (ROS)-scavenging ability was examined with ROS probes. Gene and protein expression levels of MMP-13 and IL-6 were measured via reverse transcription-quantitative polymerase chain reaction (RTqPCR), immunofluorescence, and western blotting. Twenty rats were randomly assigned to four groups: sham group, saline group, NC group, and FeOx/NC group. Except for the sham group, OA models were established by anterior cruciate ligament transection. Joint morphology was observed, and histopathological changes were evaluated by hematoxylin-eosin (HE) and Safranin O-Fast Green staining. Results TEM analysis confirmed the successful synthesis of FeOx/NC, which exhibited SOD-, CAT-, and GPx-like activities. CCK-8 and Calcein-AM/PI assays demonstrated that FeOx/NC exhibited no significant cytotoxicity towards chondrocytes. The ROS probe analysis revealed significantly reduced fluorescence intensity in the FeOx/NC+H2O2 group compared with the H 2O2 group (P < 0.05). RT-qPCR results showed that the mRNA expression levels of MMP-13 and IL-6 in the FeO x/NC+H2O2 group were significantly lower than those in the H2O2 group (P < 0.05). The results of immunofluorescence showed the fluorescence intensity of MMP-13 in the FeOx/NC+H2O2 group was significantly lower than that in the H 2O2 group (P < 0.05). Western blotting demonstrated that the protein expression levels of MMP- 13 and IL-6 were significantly decreased in the FeOx/NC+H2O2 group compared with the H2O2 group (P < 0.05). Macroscopic and histological evaluations demonstrated that FeOx/NC treatment alleviated cartilage damage compared with the saline group. Conclusion FeOx/NC nanozymes exhibit excellent biocompatibility and possess multi-enzyme catalytic activity, enabling them to efficiently scavenge intracellular ROS in chondrocytes, thereby suppressing oxidative stress and alleviating the progression of OA.